JNK pathway suppression mediates insensitivity to combination endocrine therapy and CDK4/6 inhibition in ER+ breast cancer - Sarah Alexandrou; Christine S. Lee; Kristine J. Fernandez; Celine E. Wiharja; Leila Eshraghi; John Reeves; Daniel A. Reed; Neil Portman; Zoe Phan; Heloisa H. Milioli; Iva Nikolic; Antonia L. Cadell; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract CDK4/6 inhibitors in combination with endocrine therapy are now used as front-line treatment for patients with estrogen-receptor positive (ER+) breast cancer. While this combination improves overall survival, the mechanisms of disease progression remain poorly understood. Here, we performed unbiased genome-wide CRISPR/Cas9 knockout screens using endocrine sensitive ER+ breast cancer cells to identify novel drivers of resistance to combination endocrine therapy (tamoxifen) and CDK4/6 inhibitor (palbociclib) treatment. Our screens identified the inactivation of JNK signalling, including loss of the kinase MAP2K7, as a key driver of drug insensitivity. We developed multiple CRISPR/Cas9 knockout ER+ breast cancer cell lines (MCF-7 and T-47D) to investigate the effects of MAP2K7 and downstream MAPK8 and MAPK9 loss. MAP2K7 knockout increased metastatic burden in vivo and led to impaired JNK-mediated stress responses, as well as promoting cell survival and reducing senescence entry following endocrine therapy and CDK4/6 inhibitor treatment. Mechanistically, this occurred via loss of the AP-1 transcription factor c-JUN, leading to an attenuated response to combination endocrine therapy plus CDK4/6 inhibition. Furthermore, analysis of clinical datasets found that inactivation of the JNK pathway was associated with increased metastatic burden, and low pJNKT183/Y185 activity correlated with a poorer response to systemic endocrine and CDK4/6 inhibitor therapies in both early-stage and metastatic ER+ breast cancer cohorts. Overall, we demonstrate that suppression of JNK signalling enables persistent growth during combined endocrine therapy and CDK4/6 inhibition. Our data provides the pre-clinical rationale to stratify patients based on JNK pathway activity prior to receiving combination endocrine therapy and CDK4/6 inhibition.